Subthreshold personality disorder: how feasible is treatment in primary care?. (24th March 2021) - Barber, William; Apps, Frances; Strauss, Clara; Startup, Helen; Couche, Juliet
Abstract: Individuals with subthreshold borderline personality disorder (BPD) are commonly encountered in primary care settings, yet the psychological treatments they receive are rarely tailored to their needs. In an effort to capture and treat this group of individuals in a targeted and meaningful way, some primary care settings offer Systems Training for Emotional Predictability and Problem Solving – Emotional Intensity (STEPPS-EI). This evaluation sought to assess the feasibility of STEPPS-EI within NHS primary care services. Employing an uncontrolled design, the evaluation examined recruitment, retention, effectiveness and group appraisal. Findings supported three out of four evaluation objectives for feasibility: uptake of the group was high at 74%, the group was well received by the group and significantly effective at reducing symptoms of BPD, depression and anxiety. However, retention rates were low, with only 43% classed as 'completers' of the programme. The results indicate preliminary evidence for STEPPS-EI as a potentially feasible intervention with possible modification to enhance retention and avenues for further study. Key learning aims: After reading this paper, the reader will be aware of: (1) Recent developments in the classification and diagnosis of personality disorder leading to the conceptualisation of subthreshold presentations. (2) The feasibility of conducting a primary care intervention for individuals with emotional intensity difficulties. (3) The preliminary beneficial outcomes of utilising a primary care intervention for individuals with emotional intensity difficulties. (4) Potential issues for participants and providers of primary care programmes with future direction for improvement and implementation.